The Tahlili Interpretation Method in the Discourse of the Science of Interpretation: A Study of Definitions, Terms, and Debates among Scholars - Fajar, Muhamad; Yandri Agusta Putra; Muhammad Najhan Mawahib (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2026)
This study examines the tafsir tahlili method as an analytical approach to interpreting the Qur’an in a detailed and sequential manner following the order of the mushaf, while considering linguistic features, historical context, and the circumstances of revelation. The aim of this research is to clarify the foundational concept, characteristics, strengths, and limitations of this method, as well as to reassess its relevance in contemporary Qur’anic studies. This qualitative research employs a library-based approach through an analysis of classical and modern scholarly works. The findings indicate that tafsir tahlili also known as tafsir tajzi’i plays a significant role in providing an in-depth understanding of the Qur’anic text. Its strengths lie in its thoroughness and comprehensive scope, whereas its weaknesses include a textual tendency that is less responsive to modern social issues. Scholarly debates regarding its relevance highlight the need for methodological refinement so that this approach remains adaptive to contemporary developments.